Audit Sistem Informasi E-Government Menggunakan Framework COBIT 4.1 (Studi Kasus Pada Pemerintah Daerah Kabupaten Bandung Barat) - Aditia Ramdan; Rendra Trisyanto Surya (Jurusan Akuntansi Politeknik Negeri Bandung, 2020)
In the current era of globalization, the progress of Information Technology (IT) is very rapid making Information Technology also an enabler in the Government to improve efficiency, effectiveness, transparency and accountability of government administration. West Bandung Regency Government has implemented E-Government in carrying out the administration. In its implementation, the KBB Local Government e-Government still has various problems, one of which is that the public service applications that are not integrated with the KBB Local Government e-Government. This indicates that the level of E-Government governance in the KBB Regional Government has not been maximized. Therefore, it is important to conduct an Information System Audit to assess how mature IT e-Government Governance is in the KBB Regional Government so that IT Risk does not have a broad impact. This SI audit is carried out based on the COBIT 4.1 framework, because COBIT is specifically used to measure and assess IT Governance and management of an agency or organization. This SI audit refers to 7 IT Processes related to E-Government namely, PO1, PO4, PO7, AI2, AI3, DS1, DS7, ME2 and ME4. Data collection is done by observation, interviews, gathering documentation and questionnaires in the form of KKA.